Effects of a Lactobacillus salivarius mixture on performance, intestinal health and serum lipids of broiler chickens - Shokryazdan, Parisa; Jahromi, Mohammad Faseleh; Liang, Juan Boo; Ramasamy, Kalavathy; Sieo, Chin Chin; Ho, Yin Wan (Public Library of Science, 2017)
The ban or severe restriction on the use of antibiotics in poultry feeds to promote growth has led to considerable interest to find alternative approaches. Probiotics have been considered as such alternatives. In the present study, the effects of a Lactobacillus mixture composed from three previously isolated Lactobacillus salivarius strains (CI1, CI2 and CI3) from chicken intestines on performance, intestinal health status and serum lipids of broiler chickens has been evaluated. Supplementation of the mixture at a concentration of 0.5 or 1 g kg-1 of diet to broilers for 42 days improved body weight, body weight gain and FCR, reduced total cholesterol, LDL-cholesterol and triglycerides, increased populations of beneficial bacteria such as lactobacilli and bifidobacteria, decreased harmful bacteria such as E. coli and total aerobes, reduced harmful cecal bacterial enzymes such as β-glucosidase and β-glucuronidase, and improved intestinal histomorphology of broilers. Because of its remarkable efficacy on broiler chickens, the L. salivarius mixture could be considered as a good potential probiotic for chickens, and its benefits should be further evaluated on a commercial scale.